2006
DOI: 10.1002/jor.20308
|View full text |Cite
|
Sign up to set email alerts
|

Computational comparison of reamed versus unreamed intramedullary tibial nails

Abstract: We compared, via a computational model, the biomechanical performance of reamed versus unreamed intramedullary tibial nails to treat fractures in three different locations: proximal, mid-diaphyseal, and distal. Two finite element models were analyzed for the two nail types and the three kinds of fractures. Several biomechanical variables were determined: interfragmentary strains in the fracture site, von Mises stresses in nails and bolts, and strain distributions in the tibia and fibula. Although good mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…This implies that as long as no time-progressive events are studied or quantified, the accuracy of the material properties are of minor importance within the investigated parameter space. Modeling has reached far enough that studies aim to draw conclusions that are raterelated or quantitative (Bailon-Plaza and van der Meulen, 2003; Boccaccio et al, 2008;Gomez-Benito et al, 2007;Isaksson et al, 2006aIsaksson et al, , 2007, and in those cases the quantified material properties are essential. Fig.…”
Section: Article In Pressmentioning
confidence: 99%
“…This implies that as long as no time-progressive events are studied or quantified, the accuracy of the material properties are of minor importance within the investigated parameter space. Modeling has reached far enough that studies aim to draw conclusions that are raterelated or quantitative (Bailon-Plaza and van der Meulen, 2003; Boccaccio et al, 2008;Gomez-Benito et al, 2007;Isaksson et al, 2006aIsaksson et al, , 2007, and in those cases the quantified material properties are essential. Fig.…”
Section: Article In Pressmentioning
confidence: 99%
“…The mechanical properties of cortical bone were: Young's modulus of 17,000 MPa and Poisson's ratio of 0.3. Cancellous bone properties were 700 MPa and 0.3, respectively (Duda et al, 2001;Gomez-Benito et al, 2007). The cartilage was modeled as an isotropic elastic material with a Young's modulus of 10 MPa and Poisson's ratio of 0.4 (Gefen, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The inter-fragmentary shear movement was mainly due to the relative rotation of the bony fragments around the longitudinal axis of the tibia. A finite element analysis by Gomez-Benito et al 41 compared the biomechanical performance of reamed and unreamed tibial nails. They concluded that reamed nails were superior to unreamed nails in middiaphyseal and distal tibial fractures as lower stresses were transmitted to the locking screws, reducing the risk of screw failure.…”
Section: S56mentioning
confidence: 99%
“…In general, it is expected that the stress level would decrease during the fracture healing process due to the increasing stiffness of the fracture callus. Gomez-Benito et al 41 considered the gap completely healed, and obtained a von Mises stress in the bolts of the unreamed nail of 160 MPa. In this paper a different nail, and different loading conditions, were adopted, thus the obtained results report eq.…”
Section: S56mentioning
confidence: 99%